2016
DOI: 10.1177/1049909116631550
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Association Between Multidisciplinary Home Care and Home Death Among Thai Palliative Care Patients

Abstract: Palliative home care was a significant factor enabling patients who want to die at home. We encourage health policy makers to promote the development of community-based palliative care programs in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In addition, evidence suggests that hospital visits are reduced when community-based palliative care is practiced, where caregivers provide companionship to the patient especially in duration longer than 30 days. 20 This study had a number of limitations. First, not all of the patients in this study were confirmed by genetic testing to have SCA.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, evidence suggests that hospital visits are reduced when community-based palliative care is practiced, where caregivers provide companionship to the patient especially in duration longer than 30 days. 20 This study had a number of limitations. First, not all of the patients in this study were confirmed by genetic testing to have SCA.…”
Section: Discussionmentioning
confidence: 95%
“…The studies were from Japan, 26 China, 27 Malaysia, 28 Singapore, 29,30 Thailand, 31 and South Korea. 32 Three studies were retrospective, [29][30][31] one RCT 27 and the…”
Section: Characteristics Of the Included Papermentioning
confidence: 99%
“…No limit apply 29 Cohort 55 18 27 0 Devi et al 28 Cross-sectional 62.5 0 37.5 0 Kim et al 32 Cross-sectional 75 25 0 0 Li et al 27 Randomized control trial 73 0 27 0 Nagaviroj and Anothaisintawee 31 Cohort 73 27 0 0 Tan et al 30 Cohort 64 18 18 0 remaining 3 studies were observational, 26 descriptive, 28 and cross-sectional. 32…”
Section: Pubmedmentioning
confidence: 99%
See 1 more Smart Citation
“…There are factors associated with the satisfaction of care such as relieving the symptom burden, increasing the patient's self-management of the illness, increasing the receipt of enough information to handle the emergency condition, and relieving the caregiver's burden. They stressed that home PC was an important factor for the patient's home death (11). However, there are very few studies on the aspects of the physicians' ideas, conceptions, or the effects of their ideas in PC quality.…”
Section: Introductionmentioning
confidence: 99%